Peramalan Permintaan dan Perbaikan Sistem FIFO untuk Mengurangi Kterlambatan Pengiriman Ekspor di PT.ABC - Nicholas Riyadi; Herry Christian Palit (Jurnal Titra, 2023)
PT. "ABC" is a company engaged in the field of fastmoving consumer goods. In carrying out export shipments, companies sometimes experience problems in product delivery times. This can be seen from the data obtained for shipments to Vietnam in 2022. In 2022, there will be delivery delays in August, October and November. During the observation, it was found that the cause of the delay was a lack of duplex material. The shortage of duplex material was caused by inaccurate company forecasts and inappropriate stock data due to the FIFO system not working properly. From this, a proposal is designed to overcome the problem of company forecasts and the FIFO system. Based on demand data from 2018 to 2022 for Vietnam, the best forecast method is the winter multiplicative method. This method has an error value of 11,474 for MAD, 228,642 for MSE, and 15,409% for MAPE. The design of the proposed FIFO system is carried out to reduce the occurrence of human error when inputting data and taking raw materials.